Progress in medicine and artificial intelligence. - Viniegra-Velázquez, Leonardo (Boletín Médico del Hospital Infantil de México)
This essay challenges the idea of progress as technological development in relation to medicine by focusing on people rather than things. It analyzes how the prevalence of such an idea of progress leads contemporary societies to a technofetishism that degrades community life and medical practice, contributing to the medicalization of social life. It is argued that the realization of technological potentialities depends on their forms of use, that the main motive of technological development is unlimited profit, and the priority developments are those that enhance social control which maintains the status quo. Intelligence as an intelligence quotient is criticized by proposing it as an attribute of the human being as a whole, manifested in the ways of thinking and acting of human beings in their circumstances, where affectivity and critical thinking are essential for their development; it is emphasized that its antecedent is the harmonic concert of planetary life, which contrasts with the prevailing human disharmony. It is proposed that artificial intelligence is the latest creation of technofetishism, which deposits vital attributes in technology, and that its use will accentuate the degradation of human and planetary life. Another idea of medical progress is proposed, based on forms of organization that is conducive to the development of inquisitive, critical, and collaborative skills that promote permanent improvement, whose distant horizon is dignified progress: the spiritual, intellectual, moral, and convivial sublimation of collectivities in harmony with the planetary ecosystem.